Hand Gesture Control Apps Using Hand Movements - Vidhyanjali, Gundubogula; Bhansali, Priyanka Kumari; Hiremath, S K; Rahaman, Syed Mujib (Journal of Neonatal Surgery, 2025)
This project presents an innovative and touch-free method for controlling a computer using simple hand gestures. With the help of a webcam, users can perform everyday actions—like moving the mouse cursor, clicking, scrolling, or adjusting system settings such as volume and brightness—just by waving or positioning their hands in specific ways. At the heart of this system is Mediapipe, a powerful computer vision library developed by Google. It accurately detects hand landmarks and tracks finger movements in real-time. By analyzing how the fingers are arranged, the program interprets different gestures and converts them into commands for the computer. This gesture-controlled interface not only makes computer interaction more intuitive but also enhances accessibility, especially for individuals with physical limitations or those looking for hygienic, contactless interaction. It's a meaningful step toward making human-computer interaction more seamless, inclusive, and futuristic.